Resistive Switching in Ferroelectric Bi2FeCrO6 Thin Films and Impact on the Photovoltaic Effect. (24th June 2022) - Walch, David S.; Yun, Yeseul; Ramakrishnegowda, Niranjan; Mühlenbein, Lutz; Lotnyk, Andriy; Himcinschi, Cameliu; Bhatnagar, Akash
Abstract: The multiferroic character of Bi2 FeCrO6 (BFCO), that is, the coexistence of ferroelectricity and ferromagnetism, has been predicted and demonstrated in different studies. Intriguingly, the material system also exhibits a reduced band gap, in addition to bulk‐driven photovoltaic effect. The co‐existence of all these attributes in a single system is a rare occurrence and paves way to a multitude of practical applications, with ferroelectric solar cell as one of them. In this work, epitaxially grown BFCO thin films, deposited with pulsed laser deposition on single crystalline SrTiO3 (STO) substrates, reveal a self‐ordered ionic arrangement which is proven with X‐ray and transmission electron micrcoscope (TEM) measurements. A lowered band gap and a higher conductivity lead to a superior photovoltaic performance compared to a BiFeO3 (BFO) reference film. Scanning probe microscopy (SPM) is used to test locally the ferroelectric switching properties. Poling with electric field not only caused a reliable change in the state of polarization, but also resulted in substantial changes in the resistance of the regions. Macroscopic measurements using transparent In2 O3 :Sn (ITO) electrodes demonstrate a bi‐directional multi‐stage resistive switching, which in turn influences the photovoltaic performance of the heterostucture. Abstract : This work is about the observation of resistive switching in Bi2 FeCrO6 thin films with scanning probe microscopy and macroscopic transparent top electrodes. The resistive switching is demonstrated to have a direct influence on the photovoltaic effect and associated open‐circuit voltages that potentially enable a light‐based read‐out of the electrical resistance.